Temperature-responsive silk-elastinlike protein polymer enhancement of intravesical drug delivery of a therapeutic glycosaminoglycan for treatment of interstitial cystitis/painful bladder syndrome. (October 2019) - Jensen, M. Martin; Jia, Wanjian; Schults, Austin J.; Isaacson, Kyle J.; Steinhauff, Douglas; Green, Bryant; Zachary, B.; Cappello, Joseph; Ghandehari, Hamidreza; Oottamasathien, Siam
Abstract: Interstitial cystitis (IC), also known as painful bladder syndrome, is a debilitating chronic condition with many patients failing to respond to current treatment options. Rapid clearance, mucosal coating, and tight epithelium create strong natural barriers that reduce the effectiveness of many pharmacological interventions in the bladder. Intravesical drug delivery (IDD) is the administration of therapeutic compounds or devices to the urinary bladder via a urethral catheter. Previous work in improving IDD for IC has focused on the sustained delivery of analgesics within the bladder and other small molecule drugs which do not address underlying inflammation and bladder damage. Therapeutic glycosaminoglycans (GAG) function by restoring the mucosal barrier within the bladder, promoting healing responses, and preventing irritating solutes from reaching the bladder wall. There is an unmet medical need for a therapy that provides both acute relief of symptoms while alleviating underlying physiological sources of inflammation and promoting healing within the urothelium. Semi-synthetic glycosaminoglycan ethers (SAGE) are an emerging class of therapeutic GAG with intrinsic anti-inflammatory and analgesic properties. To reduce SAGE clearance and enhance its accumulation in the bladder, we developed a silk-elastinlike protein polymer (SELP) based system to enhance SAGE IDD. We evaluated in vitro release kinetics, rheological properties, impact on bladder function, pain response, and bladder inflammation and compared their effectiveness to other temperature-responsive polymers including Poloxamer 407 and poly(lactic- co -glycolic acid)-poly(ethylene glycol). SAGE delivered via SELP-enhanced intravesical delivery substantially improved SAGE accumulation in the urothelium, provided a sustained analgesic effect 24 h after administration, and reduced inflammation. Graphical abstract: Image 1 Highlights: Temperature-responsive polymers improved intravesical drug delivery. Glycosaminoglycans exhibited analgesic and anti-inflammatory properties. Glycosaminoglycans altered polymer solution viscosity and gelation kinetics. Temperature-responsive polymer enhanced therapeutic potential of glycosaminoglycans. Soft and erodible polymer gels have less impact on bladder function.